MANAGEMENT PRACTICES AND EMPLOYEE PERFORMANCE IN ISINGIRO DISTRICT, SOUTH WESTERN UGANDA: A CASE STUDY. - Willis Nimusiima; Milton Rwangire; Robert Turyamureba (Student's Journal of Health Research, 2023)
Introduction:  The Public Service Reform in Uganda, initiated by the National Resistance Movement in 1986, aimed to improve service delivery and fulfill the promises of the People's Revolution. Still, despite efforts, inefficiency persists, as evidenced by the 2008 National Service Delivery Survey. This study, therefore, examines management practices and employee performance in local government in Uganda, a case study of Isingiro town council.  Methodology:  The study utilized a case study design, collecting qualitative and quantitative data through focus group discussions, interviews, and questionnaires from government employees, obtaining ethical clearance from the Bishop Stuart University Research and Ethics Committee. Results: Results indicated that 23 (57.5%) were permanent/probationary town council employees, 10 (25%) were political leaders and 7 (17.5%) were casual workers. From the results on the relationship between effective communication and employee performance, 19(48%) of respondents strongly agreed, 20 (50%) agreed while 1(2%) disagreed that there`s no timely flow of information.  Conclusion: Effective communication has a significant positive effect on employee performance. Therefore, if there is effective communication, the resultant situation greatly improves employee performance. However, some employees noted a few gaps like no timely flow of information. These areas must be addressed for effective communication to prevail and improve employee performance. Furthermore, it is also noted that informed decision-making through meetings, expressing innovative suggestions to senior management, regular discussions, taking all decisions by consensus, and working as a Teamwork has a positive and significant relationship on employee performance. Recommendations:  Management should involve all employees in employee performance to maximize productivity. Avoid departmental heads' infrequent sharing of information. Performance measurement through goal setting and appraisal increases productivity, but there's a gap in assessing employees according to their targets that need to be addressed.